A new species of dwarf sea bass, genus Serranus (Serranidae: Actinopterygii), from the southwestern Atlantic Ocean - Carvalho Filho,Alfredo (2013)
Serranus aliceae n. sp. is described from Rio de Janeiro and Espírito Santo States, southeastern Brazilian coast. The species is readily distinguished from its congeners by the following combination of characters: scales around the caudal peduncle 20 or 21; total gill rakers on first branchial arch 23-29; cheek-scales rows 5 or 6; and by the coloration of live specimens, which are reddish with a broad, conspicuous, white stripe from post-orbital region to the caudal-fin base and a white abdomen. The new species apparently inhabits the deeper (30 or more meters) portions of reef environments along the subtropical Brazilian coast, and is possibly associated with upwelling cold-water masses. The species was observed hovering above rocky bottoms, feeding on micro-crustaceans, squid larvae, and zooplankton. This new species increases to eight the number of valid Serranus species recorded in the southwestern Atlantic.